Pengaruh Pengelolaan Kelas dan Profesionalisme Guru terhadap Prestasi Belajar Siswa - Marlina Marlina; Happy Fitria; Yenny Puspita (ISEJ : Indonesian Science Education Journal, 2020)
This study aims to: 1) analyze the effect of classroom management on student achievement; 2) to analyze the effect of teacher professionalism on student achievement; 3) to analyze the effect of classroom management and teacher professionalism together on student achievement. This research uses quantitative methods. Data collection was carried out by means of a questionnaire and documentation. Data were analyzed descriptively using SPSS version 16 for windows. From the results of the study it can be concluded that: 1) there is an effect of class management on student achievement in SMP Negeri Babat Supat District where the value of tcount> tcount or 2.998> 1.669 with linear regression equation Y = 33.470 + 0.486X1 and the contribution of class management is 43.2 %; 2) there is an effect of teacher professionalism on student achievement where the value of tcount> tcount or 3.012> 1.669 with a linear regression equation 32.704 + 0.480X2 and the contribution of classroom management is 45.4%, and 3) there is a significant influence between classroom management (X1) , and teacher professionalism (X2) on student achievement (Y) where the value of Fcount> Ftable or 17.786> 3.14 with the regression equation Y = 19.838 + 0.325X1 + 0.322X2 The coefficient of determination R2 (R Square) is 0.393 which means that management class and teacher professionalism were able to influence student achievement with a contribution of 39.3%.